Fibrous Bundles in Biomorph Systems: Surface‐Specific Growth and Interaction with Microposts. Issue 4 (10th June 2021) - Knoll, Pamela; D'Silva, Denvert S.; Adeoye, Damilola I.; Roper, Michael G.; Steinbock, Oliver
Abstract: The front cover artwork is provided by the Steinbock group at Florida State University. The image shows a pseudo‐color micrograph of biomorph bundles (cyan) pushing a resin disk (red/cyan) as well as other, partly helical, structures (green). Biomorphs consist of nanostructured BaCO3 and silica. Read the full text of the Article at 10.1002/syst.202000061 . Abstract : "Biomorphs are purely inorganic, smoothly curved microstructures and consist of co‐aligned BaCO3 nanorods as well as amorphous silica. The cover graphic is a pseudo‐color representation of an optical micrograph. It shows the newly reported biomorph bundles (cyan) that during growth push and flip small resin disks (red/cyan) that initially adhered to the substrate. Additional, partly helical, biomorphs are highlighted in green. The cover profile provides more information on the motivation and novelty of this study and the design of the artwork…" This and more about the story behind the front cover can be found in the Article at 10.1002/syst.202000061 .